CLINICAL AND NEUROSYCHOLOGICAL CHARACTER OF DISORDERS IN CHILDREN WITH DYSLEXIA - Djurabekova Aziza Taxirovna; Shodmonov Asilbek Otabekovich; Gaybiev Akmal Akhmatjonovich; Mamurova Mavlyuda Mirxamzaevna (Scholar Express Journals, 2021)
One of the first descriptions of dyslexia in children belongs to Morgan, where a teenager with preserved intelligence found it difficult to read (1, 3). Reading itself is written speech, and is formed later than oral speech, consisting of the interaction of cognitive systems and a series of functions. The reading process goes through the stage of decoding and reading comprehension. Dyslexia is caused by a large number of factors, but the main ones are genetically determined periods of development of ontogenesis or as a result of insufficiency of certain brain structures, brain immaturity (2, 6). Numerous literary sources confirm the interest of scientists in the problem of dyslexia. A special section of diagnostics, starting from the last century, is the results of autopsy and neuroimaging data, a wide range of studies of the bioelectrical activity of the brain, a separate section of the psychological analysis of children with dyslexia (4, 8). In recent years, with the advent of a large selection of pharmacological drugs, modern medicine points to general recommendations and the feasibility of therapeutic treatment of patients with dyslexia, to improve the quality of patients with dyslexia, a normal lifestyle with the achievement of the level of development of reading skills, addressing the issue of social well-being of the future generation (5 , 7).
Keywords: Dyslexia; Neurological Nature; Neuropsychological Character